Talabalardıń sociallıq beyimlesiwinde kommunikativ kónlikpelerdi rawajlandırıwdıń áhmiyeti - Risnazarova, A.R (ILIM hám JÁMIYET, 2024)
The article provides examples of the development of communication skills among students as a means of social adap-